2004
DOI: 10.1046/j.0905-6157.2003.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of nitrites in breath condensates and lung function in asthmatic children

Abstract: We aimed to evaluate the value of exhaled breath condensates in monitoring airway inflammation in childhood asthma before and after high altitude climate therapy. Forty-eight asthmatic children on regular anti-asthma treatment with a normal FEV1 and positive skin prick test for house dust mites were recruited. All children had been referred to an alpine clinic for high altitude climate therapy, because of persistent asthmatic symptoms despite use of daily anti-inflammatory treatment. Subjects were assessed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
4
24
1
2
Order By: Relevance
“…These results are in line with a recently published study in asthmatic children [28]. Especially patients with severe asthma, profit from high-altitude climate therapy without any need to increase systemic GC doses.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in line with a recently published study in asthmatic children [28]. Especially patients with severe asthma, profit from high-altitude climate therapy without any need to increase systemic GC doses.…”
Section: Discussionsupporting
confidence: 82%
“…In the opposite direction, the study of VERKLEIJ et al [14] brought the pooled SMD down to the greatest degree: when excluded, the overall SMD increased to 0.60 (95% CI 0.49-0.70). When excluded, the only study that had reported lung function as a median rather than as a mean value [30] did not substantively change the observed overall SMD (0.55, 95% CI 0.45-0.65). We also wished to calculate SMD for studies performed at altitudes of >2500 MASL, which is an accepted threshold for high altitude.…”
Section: Resultsmentioning
confidence: 99%
“…Weighted mean difference KOLESAR et al [19] BONER et al [20] BRIMKULOV (1) [22] BRIMKULOV (2) [22] PIACENTINI et al [23] SIMON et al [24] ALLEGRA et al [11] BONER et al (1) [25] BONER et al (2) [25] KOKOV [26] VAN VELZEN et al [12] VALLETTA et al [27] GROOTENDORST et al [28] PERONI et al [29] STRAUB et al [30] HUISMANS et al [ …”
mentioning
confidence: 99%
“…In children with asthma, the technique has demonstrated increased leukotrienes, interleukin-4, 8-isoprostane, aldehydes and glutathione when compared with controls [7][8][9][10]. The effects of treatment on EBC in asthma include a reduction in nitrites in association with altitude in the Swiss Alps [11], and a reduction in cysteinyl leukotrienes, 8-isoprostane, aldehydes and glutathione during systemic corticosteroid treatment of an acute exacerbation [10,12]. However, there has usually been significant overlap between cases and controls, and no marker has, so far, demonstrated sufficient independence to assist with the diagnosis or treatment in children.…”
mentioning
confidence: 99%